Structural, petrological and chemical analysis of syn‐kinematic migmatites: insights from the Western Gneiss Region, Norway. (10th April 2014) - Ganzhorn, A. C.; Labrousse, L.; Prouteau, G.; Leroy, C.; Vrijmoed, J. C.; Andersen, T. B.; Arbaret, L.
Abstract Evidence of melting is presented from the Western Gneiss Region (WGR) in the core of the Caledonian orogen, Western Norway and the dynamic significance of melting for the evolution of orogens is evaluated. Multiphase inclusions in garnet that comprise plagioclase, potassic feldspar and biotite are interpreted to be formed from melt trapped during garnet growth in the eclogite facies. The multiphase inclusions are associated with rocks that preserve macroscopic evidence of melting, such as segregations in mafic rocks, leucosomes and pegmatites hosted in mafic rocks and in gneisses. Based on field studies, these lithologies are found in three structural positions: (i) as zoned segregations found in high‐P (ultra)mafic bodies; (ii) as leucosomes along amphibolite facies foliation and in a variety of discordant structures in gneiss; and (iii) as undeformed pegmatites cutting the main Caledonian structures. Segregations post‐date the eclogite facies foliation and pre‐date the amphibolite facies deformation, whereas leucosomes are contemporaneous with the amphibolite facies deformation, and undeformed pegmatites are post‐kinematic and were formed at the end of the deformation history. The geochemistry of the segregations, leucosomes and pegmatites in the WGR defines two trends, which correlate with the mafic or felsic nature of the host rocks. The first trend with Ca‐poor compositions represents leucosome and pegmatite hosted in felsic gneiss, whereas the second group with K‐poor compositions corresponds to segregation hosted in (ultra)mafic rocks. These trends suggest partial melting of two separate sources: the felsic gneisses and also the included mafic eclogites. The REE patterns of the samples allow distinction between melt compositions, fractionated liquids and cumulates. Melting began at high pressure and affected most lithologies in the WGR before or during their retrogression in the amphibolite facies. During this stage, the presence of melt may have acted as a weakening mechanism that enabled decoupling of the exhuming crust around the peak pressure conditions triggering exhumation of the upward‐buoyant crust. Partial melting of both felsic and mafic sources at temperatures below 800 °C implies the presence of an H2O‐rich fluid phase at great depth to facilitate H2O‐present partial melting.